The reasons why the Public-Private Partnership contracts regime should be preferred to Government-to-Government (G2G) agreements in Peru - Sheput Stucchi, Humberto (2023)
The success attained in the development of the essential infrastructure for the XVIII Pan American Games and the Sixth Parapan American Games of Lima 2019 has demonstrated a distinct shift in the approach embraced by the Peruvian State in the execution of infrastructure ventures. The utilization of public-private partnership contracts has been relinquished in favor of government-to-government agreements.Is the idea or alternative of prioritizing Government-to-Government agreements as the initial option the most suitable or advantageous for the Peruvian State? In this article, we will assess the benefits and drawbacks of both approaches and propose criteria to evaluate which scheme would be the most favorable depending on the nature of the project or infrastructure to be undertaken.